PENGARUH IKLIM BELAJAR DI KELAS TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP N 2 SUNGAI PUA KABUPATEN AGAM - Nuraida Fatma; Puti Andam Dewi (Jurnal Salome : Multidisipliner Keilmuan, 2025)
Achieving educational goals at school requires a learning climate that is conducive to participating in learning as part of the school education system. The school as an organization and educational institution whose components consist of students, educators and educational staff, requires a conducive atmosphere as a collective consistency that must be implemented, in order to realize the vision, mission and goals of education in schools. Likewise, students need a conducive learning atmosphere that reflects positive relationships between all elements of the school. Apart from that, the formulation of the problem in this research is: "Is there an influence of the learning climate in the classroom on student learning outcomes in PAI subjects in class VII at SMP Negeri 2 Sungai Pua". The aim of this research is to describe the classroom learning climate on student learning outcomes and to examine the influence of the classroom learning climate on student learning outcomes in PAI subjects in class VII at SMP N 2 Sungai Pua. Based on the results of the discussion regarding the influence of the learning climate in the classroom on student learning outcomes in Islamic religious education subjects at SMP N 2 Sungai Pua, Agam Regency, several conclusions can be drawn as follows. There is an influence of the learning climate variable on the learning outcomes of class VII students at SMP N 2 Sungai Pua. . This is proven by the results of the hypothesis test, namely with a standard deviation of 69 respondents, a T table of 1.667 was obtained. Seen from the table above, a significance value of 0.000 ≤ 0.05 was obtained and T count≥ T table, namely 3.898≥ 1.667. In accordance with the criteria tcount≥ ttable, H0 is rejected and Ha is accepted, meaning that there is a significant influence of the classroom learning climate on student learning outcomes in PAI subjects in class VII of SMP Negeri 2 Sungai Pua, Agam Regency. So it can be said that the learning climate in the classroom will improve student learning outcomes. It can be said that the learning climate has a positive influence on student learning outcomes. In other words, the learning climate variable in the classroom has an influence of 43% on student learning outcome variables and 57% is influenced by a bad learning environment and neglected discipline.